Penanaman Nilai Kebersihan melalui Pembiasaan Membuang Sampah pada Siswa Kelas I MI Daarul Ikhwan - Rezky Firmansyah; Dinda Salsanita; Maria Kunera Koe; Wilfridus Ferdinand Aco; Rizky Juliani; Muhammad Fatur Rohman; Danil Fakhri; Luthfi Hardiayanto (Pusat Riset dan Inovasi Nasional, 2026)
Instilling clean living habits from an early age is crucial for developing disciplined and responsible student character. This community outreach activity was conducted to provide understanding and habituate students to always dispose of trash properly. The target of this community outreach activity was elementary school-aged children at MI Daarul Ikhwan Kelapa Dua Wetan, Ciracas District, East Jakarta City. The activity was carried out through direct delivery of material in simple language, engaging educational games, practical examples of sorting organic and inorganic waste, and the application of cleanliness habits in daily classroom activities. throughout the activity, students demonstrated enthusiasm and active participation in each series of activities. The result of the activity showed an increase in awareness and changes in students’ behavior in maintaining the classroom environmental. Students began to get used to disposing of trash properly without having to be reminded by the teachers. It is estimated that this habit can continue to be implemented and become a positive culture, both in the school environmental and at home.